Penyuluhan Hukum Mengenai Perlindungan Hukum Terhadap Anak Di SMP Negeri 41 Bandar Lampung - Siregar, Naek; Azizah, Siti (Faculty of Law, Universitas Pattimura, 2024)
Introduction: : Legal counseling on child protection at SMP Negeri 41 Bandar Lampung is an effort to increase the understanding and awareness of students, teachers and parents regarding the importance of protecting children's rights and welfare in the context of education. The counseling covered various aspects, including children's basic rights, violence prevention, safe use of technology, and concrete actions in reporting and responding to situations that threaten children's safety. The counseling began by discussing children's basic rights in accordance with national and international law. Students are given an in-depth understanding of the right to life, education, and protection from various forms of exploitation and violence.Purposes of Devotion: The purpose of this service activity is to provide increased awareness and understanding of legal protection of children in the environment of SMP Negeri 41 Bandar Lampung. Method of Devotion: The method used in the implementation of activities in the village of SMP Negeri 41 Bandar Lampung, Panjang Subdistrict is in the form of providing material with the speaker explaining all the material in front of the students.Results of the Devotion: Basically, the students of SMP Negeri 41 Bandar Lampung have more or less understood the legal protection of children. This can be seen by the large number of participation and enthusiasm of the students of SMP Negeri 41 Bandar Lampung who asked questions and participated in discussions in the legal counseling. Students have the opportunity to know how legal protection a child has, including the implementation of legal protection of children that occurs at school.